Planejamento e determinação de áreas de conflitos de usos na zona urbana de Cruz Alta - RS - Nogueira, Bárbara Tatiane Martins Vieira (2010)
The current urban issues related to urban and territorial planning are powerful tools found in Geoinformation, analyzing the changes caused by man, materializing subsidies increasingly reliable for the observation of damage to the environment. The misuse and indiscriminate use of natural resources causes environmental deterioration, uncontrolled growth of cities potentiates problems such as deforestation, construction in inappropriate areas and also pollution. This study, conducted in the urban area of Cruz Alta, located in the northwestern region of Rio Grande do Sul, for purpose of identifying, according to environmental legislation, the Permanent Preservation Areas (PPA), to identify the impacts by human action in these areas. For determination of PPA were used geospatial technologies. Layers were integrated into a structured database (GIS) and proceeded to survey of land use, drainage, slope and road system. To this end, we used the sensor Ikonos images, topographic maps and GPS. The urban area of Cruz Alta has environmental problems, which showed deposition of waste in inappropriate locations, households in risk areas, sewage released into streams. The PPA, are of extreme importance for the whole population and we must preserve them, because the inappropriate use of renewable resources cause serious and even dramatic consequences for the population as regards the pollution of rivers, deforestation and soil erosion. For the preservation of these areas should be created joint actions among government agencies and the general population.